A new variation of modern prejudice: young Korean men's anti-feminism and male-victim ideology - Jung, Han Wool (Frontiers in Psychology, 2023)
In South Korea, anti-feminism is now rapidly spreading through the Internet among young men, and they started to identify themselves as a social minority or "victims" of female power. Despite their ramification to present South Korea, theoretically discussing, they are indistinct from the racism and sexism of White men that emerged at least a half-century ago.In this view, they share the same root of typical modern racism or sexism, although they look novel in phenomena. Such a hypothesis was buttressed by the quantifying their attitudes towards various outgroups based on the transference of prejudice theory. Moreover, the subtle sexist undertones hidden in their arguments were discussed by various psychological theories and empirical data/statistics. Additionally, various potential factors that may shape or accelerate their attitudes or behaviors were discussed on the basis of the threat-defense theory (Jonas et al., 2014). Through comprehensive literature review based on this theory, I propose the features related to Korean anti-feminism encompassing behavioral/situational (overindulging violent or degrading Internet contents, verbal aggression), relational/epistemic (ostracism, attachment insecurity, pseudo-rationalism), and group-level (provocative interactions, polarization) attributes, some of which may also influence other groups than young men and ingrain or exacerbate extreme ideologies of other groups, including young women. Scrutinizing Korean online anti-feminism and male-victim ideology will help in understanding the psychological origins of various social extremities or radical ideologies beyond cultural barriers.